"He's under oath": Privacy and Confidentiality Views Among People Who Inject Drugs Enrolled in a Study of Social Networks and Human Immunodeficiency Virus/Hepatitis C Virus Risk. (July 2021) - Abadie, Roberto; Fisher, Celia; Dombrowski, Kirk
Despite the promise of social network research, this method raises important ethical questions regarding privacy and confidentiality. Although researchers and bioethicists have considered research obligations in relation to marginal or vulnerable populations, the views of people who inject drugs (PWIDs) have not been sufficiently considered. To elicit participants' views of research obligations, we conducted in-depth interviews with a subset ( n = 40) of active PWIDs enrolled in a large social network study. Findings suggest participants have an expectation of confidentiality but believe this obligation need not be absolute and can be waived if a participant violates community norms or place others at risk. Ethics boards should recognize that marginalized populations are able to articulate complex moral views about privacy and confidentiality. Engaging participants in dialogue about the responsible conduct of research presents an opportunity to correct under- or overestimations of research vulnerabilities when such decisions are restricted to the perspectives of investigators or Institutional Review Board members.